PENGARUH PENGGUNAAN METODE PEMBELAJARAN BERBASIS MASALAH TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SMA PGRI 2 TAMALATE - Nurhayati; Kamaruddin, Syamsu A (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using the Problem-Based Learning (PBL) method on students’ critical thinking skills at SMA PGRI 2 Tamalate. The research employed a quantitative approach with a quasi-experimental design using the Pretest-Posttest Control Group Design. The population consisted of all eleventh-grade students at SMA PGRI 2 Tamalate in the 2024/2025 academic year, totaling 120 students, with a sample of 60 students divided into two groups: an experimental class taught using the Problem-Based Learning method and a control class taught using conventional methods. Data were collected through a critical thinking test that had been validated and tested for reliability. The results showed that the mean posttest score of the experimental class was higher than that of the control class. The t-test results indicated a Sig. (2-tailed) value of 0.000 < 0.05, meaning there was a significant difference between the two groups. Furthermore, the correlation analysis yielded an r value of 0.721 with Sig. = 0.000, indicating a positive and strong relationship between the implementation of Problem-Based Learning and students’ critical thinking skills. Therefore, it can be concluded that the Problem-Based Learning method significantly improves students’ critical thinking skills.